Pengaruh Pemahaman Literasi Keuangan dan Risiko Investasi terhadap Minat Investasi Mahasiswa - Handika Prima Tarigan; Fera Damayanti; Syarif M. Helmi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Financial literacy and investment risk on the investment interest of students in the Accounting Study Program, Faculty of Economics and Business, Tanjungpura University. The main problem studied is the low level of financial literacy among students, which, based on financial literacy index data, only reaches 56.42%, far below other productive community groups. This is feared to influence students' minimal interest in investing. Using an associative quantitative approach, this study tests hypotheses and analyzes the relationship between variables. The research sample consisted of 77 active sixth-semester students, selected using a purposive sampling technique with the criterion of having taken financial management courses. Data were collected through questionnaires and analyzed using SPSS software. The results of the multiple linear regression test indicate that financial literacy and investment risk partially and simultaneously have a positive and significant influence on students' investment interest. The coefficient of determination (R2) of 67.2% indicates that these two variables are the dominant factors influencing students' investment interest. The conclusion of this study is that understanding financial literacy and awareness of investment risks are very important to encourage students' interest in investing.